2021
DOI: 10.1016/j.ijppaw.2021.10.004
|View full text |Cite
|
Sign up to set email alerts
|

Tick abundance and life-stage segregation on the American black bear (Ursus americanus)

Abstract: Tick abundance and diagnosed cases of tick-borne diseases have been increasing in the United States. American black bear ( Ursus americanus ) populations have also been increasing in the eastern United States. As a competent host of several species of ticks and a mammal capable of traveling long distances, the role of black bears as hosts for ticks requires further evaluation. Ectoparasite surveys were conducted on black bears in Pennsylvania to evaluate tick presence, abundance, spatial… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 30 publications
1
7
0
Order By: Relevance
“…Cats were more successfully parasitized by I. scapularis which preferred the head and A. americanum, which preferred the tail and perianal region 19 . This is similar to a study of tick distribution on wild black bears ( Ursus americanus ) in Pennsylvania, indicating that the primary tick present was I. scapularis and that the greatest numbers were found in association with the ears and muzzle 20 . In these cases, the ability for ticks to attach to specific areas is most likely a result of the grooming habits and abilities of the animals in question.…”
Section: Discussionsupporting
confidence: 86%
“…Cats were more successfully parasitized by I. scapularis which preferred the head and A. americanum, which preferred the tail and perianal region 19 . This is similar to a study of tick distribution on wild black bears ( Ursus americanus ) in Pennsylvania, indicating that the primary tick present was I. scapularis and that the greatest numbers were found in association with the ears and muzzle 20 . In these cases, the ability for ticks to attach to specific areas is most likely a result of the grooming habits and abilities of the animals in question.…”
Section: Discussionsupporting
confidence: 86%
“…Although there were multiple tick species frequently reported on animals, a number of cases found that animals can be infested by a single tick species. For example, a survey of tick abundance on American black bears ( Ursus americanus ) found that all 1976 ticks collected from multiple areas of 278 black bears were identified as I. scapularis ( Tiffin et al, 2021 ). An early case reported more than 2000 ticks as Haemaphysalis warburtoni from a two-year old giant panda in a natural reserve in Sichuan, China ( Wu and Hu, 1985 ).…”
Section: Discussionmentioning
confidence: 99%
“…Regarding the life stage of ticks, according to previous studies, adult ticks were usually found from mammals with medium to large body size ( Bouchard et al, 2013 ). For example, 98% and 100% of I. scapularis collected from the ear area and upper spine of black bears were adults ( Tiffin et al, 2021 ). In our study, all the ticks were collected from the ear area of the giant panda and identified as adults.…”
Section: Discussionmentioning
confidence: 99%
“…from harvested game animals at check stations, so providing these data and ectoparasites to researchers would require little additional effort on their part. Furthermore, since they are quickly processing through many animals to satisfy their clientele, having professional wildlife accessors search for ectoparasites using an efficient systematic method (timed or by body section) may help them prioritize ectoparasite collection within their normal data collection or processing duties [ 22 , 73 , 76 ].…”
Section: Professional Wildlife Accessmentioning
confidence: 99%
“…This does not necessarily mean that the researcher finds and pursues the wildlife themselves, although researchers have reported harvesting animals for research in some cases [ 82 ]. Instead, most studies sampled game animals at hunter check stations, deer processors, and other high-volume recreational user areas to collect ectoparasites [ 60 , 63 , 76 , 83 , 84 , 85 , 86 , 87 , 88 , 89 , 90 , 91 , 92 , 93 , 94 , 95 , 96 , 97 , 98 , 99 , 100 , 101 , 102 , 103 , 104 , 105 ]. In this case, hunters would bring harvested animals to a central location and, then, as part of the animal checks or processing, researchers could search the animal for ectoparasites using an established systematic method.…”
Section: Recreational Wildlife Accessmentioning
confidence: 99%